Beyond Subsistence: How Livelihood Assets Shape Farmers’ Crop Preferences in Community Forest Areas of Maros, Indonesia: Melampaui Kebutuhan Subsisten: Bagaimana Aset Penghidupan Membentuk Preferensi Tanaman Petani di Kawasan Hutan Komunitas di Maros, Indonesia - Dian Ayu Lestari Hasannudin; Supratman; Makkarennu; Adrayanti Sabar; Baginda Hamzah; Zarah Arwieny Hanami (JURNAL HUTAN TROPIKA, 2026)
This study examines how the livelihood assets of farmers managing land within Community Forest areas influence their crop preferences in Laiya Village, Maros Regency, Indonesia. Using the Sustainable Livelihood Framework, farmers’ preferences were categorized into two groups: crops currently cultivated and crops they intend to develop. The data collected covered household livelihood conditions, including expenditures for activities within and outside the Community Forest area, total household expenditures, and income and earnings from both forest-based and non-forest sources. The findings show that the main commodities produced within the Community Forest area are pine resin and honey, while outside the forest area farmers cultivate rice, peanuts, porang, and ginger, as well as raise livestock such as cattle and poultry. In terms of average income contribution, pine resin accounts for approximately 27 % and is the largest source of income from the Community Forest area. However, overall, the average income generated from outside the forest area is still higher than income from Community Forest sources. As a result, most farmers prefer to expand rice and peanut cultivation outside the forest area, as these activities are perceived to be more profitable and provide more stable income. These findings suggest that farmers’ choices are influenced not only by basic subsistence needs but also by the pursuit of higher and more stable income. Limited financial and physical assets, such as low bargaining power and restricted access to pine resin sites, drive their focus on food crops outside the forest. Strengthening infrastructure, capacity building, and value-added forest product development are needed to enhance livelihoods.